2020
DOI: 10.1186/s12904-020-00548-7
|View full text |Cite
|
Sign up to set email alerts
|

The desire to die in palliative care: a sequential mixed methods study to develop a semi-structured clinical approach

Abstract: Background: Although desire to die of varying intensity and permanence is frequent in patients receiving palliative care, uncertainty exists concerning appropriate therapeutic responses to it. To support health professionals in dealing with patients´potential desire to die, a training program and a semi-structured clinical approach was developed. This study aimed for a revision of and consensus building on the clinical approach to support proactively addressing desire to die and routine exploration of death an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 51 publications
0
41
0
3
Order By: Relevance
“… 41 , 42 Early and open discussions may strengthen therapeutic relationships and help PCPs to determine when they may need to refer patients for additional specialist consultations or other supporting services. 48 , 50 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 41 , 42 Early and open discussions may strengthen therapeutic relationships and help PCPs to determine when they may need to refer patients for additional specialist consultations or other supporting services. 48 , 50 …”
Section: Discussionmentioning
confidence: 99%
“… 5 As people live and experience illnesses and end-of-life journeys in relationships and communities, a clearer understanding of patient motivations in their personal and relational contexts by clinicians can facilitate discussions of available support and resources to meet these goals. Using semi-structured conversational guides to uncover the wider context of the patient’s suffering early on as an upstream measure may help PCPs to build trust and clarify ambiguous statements, 50 explain the palliative care philosophy, and offer targeted treatments and support resources to address symptoms and suffering holistically. As a German study revealed, in strengthening therapeutic relationships with patients who express a desire to hasten death, PCPs can help to ease patients’ suffering by generating hope and new perspectives through refocusing or activating patients’ mental and social resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 , 20 , 41 43 The request for euthanasia can constitute a call for help. 44 , 45 If this is taken properly into consideration, it can decrease the overall suffering or even hinder the move to a suicidal act. 44 Furthermore, euthanasia requests call into question the care and support of PCU teams.…”
Section: Discussionmentioning
confidence: 99%
“… 47 It is thus important for HCPs to be trained in accompanying these difficult discussions, to become able to proactively initiate them, and to build a trusting relationship with their patient. 45 , 48 …”
Section: Discussionmentioning
confidence: 99%